Sustainable tourism development in upang river based on MSP+DM analysis - Marissa Pusparini; Kunkun Kurniawan; Iga Safa Marwani; Muhtadin Muhtadin (Jurnal Pariwisata Pesona, 2024)
Sungai Upang is a 40-hectare biodiversity conservation area situated in Tanah Bawah Village, Puding Besar Sub-district, Bangka Regency, Bangka Belitung Islands Province. The Upang River biodiversity area has biodiversity and is an ecological environment that must be maintained. This area is a source of raw water for the needs of the surrounding community. The landscape of the Upang River area is an attraction in the development of education-based sustainable tourism related to nature conservation as well as a research center related to flora and fauna in the Bangka Belitung Islands. On the other hand, some threats can interfere with the sustainability of this biodiversity conservation area, including forest fires, illegal logging, and the expansion of oil palm plantations. This research aims to find out the variables of marketability, sustainability, participation, and disaster mitigation abbreviated as MSP + DM,Â  and sustainable tourism development steps in the Upang River biodiversity area.Â  The research design chosen was qualitative research. Data were collected through observation, in-depth interviews, and focus group discussions to obtain the value parameters of the MSP+DM variables. Furthermore, the data were analyzed to classify them into embryonic, pilot, growing, and independent criteria scores. Based on the research results, the Upang River biodiversity area has tourism products that can attract tourists. Overall, the assessment of marketability, sustainability, participatory, and disaster mitigation variables for the Upang River biodiversity area as a sustainable tourism destination is in a pilot category. Tourism development steps are directed towards developing sustainable tourism products thematically, minimizing permanent physical development, regulating the number of visits according to capacity, and limiting the use of existing natural resources around.